Integrating Problem-Based Learning and SSI-ESD Context to Foster Chemical Literacy and Environmental Awareness in Secondary Education - Putri, Siska Widiana; Handayani, Sri; Ramadanty, Restyani (Jurnal Pendidikan MIPA, 2025)
This study aimed to examine the differences in students’ chemical literacy and environmental awareness, both jointly and separately, between those taught using problem-based learning (PBL) contextualized with Socio-Scientific Issues and Education for Sustainable Development (SSI-ESD) and those taught using a conventional scientific approach on the topic of climate change. The integration of PBL, SSI, and ESD creates a synergistic learning model that emphasizes real-world problem-solving, critical thinking, and sustainability awareness, which are essential competencies for 21st-century learning. A quasi-experimental design with a pre-test and post-test control group was employed to ensure a valid comparison. The research involved 144 Grade X students from two public senior high schools in Yogyakarta City, selected using class-level random sampling, consisting of two experimental classes (n = 72) and two control classes (n = 72). The experimental group was taught using a PBL-based SSI-ESD approach, while the control group received instruction through a traditional scientific approach. Research instruments included a validated chemical literacy test and an environmental awareness questionnaire. Data were analyzed using N-gain, MANOVA, and descriptive statistics to assess both improvement and effect size. The findings revealed significant differences in students’ chemical literacy and environmental awareness between the two groups, as determined by MANOVA (Hotelling’s Trace = 0.392; p < 0.05). The experimental group achieved higher N-gain scores in chemical literacy (0.52) and environmental awareness (0.53) compared to the control group (0.39 and 0.31, respectively). This learning approach demonstrated a large effect size on both skills simultaneously (0.282) and separately (0.183; 0.240). These results indicate that PBL-based SSI-ESD learning effectively enhances both students’ chemical literacy and environmental awareness while supporting the implementation of current educational policies that promote Education for Sustainable Development (ESD) and competency-based learning in Indonesia, aligning with the Merdeka Belajar curriculum framework.   Keywords: chemical literacy, environmental awareness, PBL-SSI-ESD, student worksheet, climate change.